Physical and mechanical properties of Acacia Mangium x Acacia Auriculiformis hybrid (acacia hybrid) and Acacia Mangium Superbulk planted in Sarawak - Ismail, Jusoh; Farawahida, A. Z (Conference of Forestry and Forest Products Research (CFFPR), 2007)
Recently two new wood materials were introduced in Sarawak, namely Acacia mangium x Acacia auricu/iformis (Acacia hybrid) and Acacia mangium superbulk (A. mangium superbulk) which have desirable characteristics of rapid growth rates and greater resistance to heart rot. Studies of their basic characteristics are important for future utilization. The objectives of this study were to determine the physical and mechanical properties and to compare the properties among A. mangium, A. auriculiformis, A. hybrid and A. mangium superbulk. Acacia trees of six years age were studied and sampled by cutting at dbh, 50%,70% and 90% heights of the clear bole. The basic densities of A. auricuJiformis, A. mangium, A. hybrid and A. mangium superbulk were 636, 464,472 and 334 kg m-3 respectively, and statistically the basic densities of A. hybrid and A. mangium were similar. Volumetric shrinkages for all acacias ranged between 14.39 and 15.99% and the differences were not statistically different Static bending test showed that the modulus of rupture (MOR) of A. 2 auriculiformis was 89 N mm- , A. hybrid 85 N mm-z, A. mangium 78 N mm-2 and A. superbulk 55 N mm-z. For compression parallel to grain, the maximum crushing strength (MCS) of A. hybrid was the highest (62 N mm2), fallowed by A. auriculiformis (59 N mm2), A. mangium (53 N mm-2) and A. mangium superbulk (50 N mm-2). Further analyses revealed that the MOR, MOE and MCS among A. mangium, A. auricu/iformis and A. hybrid were not statistically different. However, the strength properties of A. mangium superbulk were significantly lower compared with A. mangium, A. auriculiformis and A. hybrid. It can be concluded that improvements of Acacia hybrid and A. mangium superbulk are only confined to growth characteristics and heart-rot resistance but not wood properties.